2008
DOI: 10.1063/1.2940325
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric pressure air plasma jet for medical applications

Abstract: By flowing atmospheric pressure air through a direct current powered microhollow cathode discharge, we were able to generate a 2 cm long plasma jet. With increasing flow rate, the flow becomes turbulent and temperatures of the jet are reduced to values close to room temperature. Utilizing the jet, yeast grown on agar can be eradicated with a treatment of only a few seconds. Conversely, animal studies show no skin damage even with exposures ten times longer than needed for pathogen extermination. This cold plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
211
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(220 citation statements)
references
References 27 publications
2
211
0
7
Order By: Relevance
“…Studies investigating the interaction of plasma jets with living cells have shown eradication of pathogens (Goree et al, 2006;Kolb et al, 2008;Stoffels et al, 2006), blood coagulation Kalghatgi et al, 2007;Kieft et al, 2005), tissue sterilization Shashurin et al, 2008), and the ablation of cultured liver cancer cells (Zhang et al, 2008). The effects of cold atmospheric plasma were shown to be due not to heat, but to active species, mainly oxygen/hydroxyl radicals and nitric oxide, generated in the plasma or in the tissue brought into contact with the plasma (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the interaction of plasma jets with living cells have shown eradication of pathogens (Goree et al, 2006;Kolb et al, 2008;Stoffels et al, 2006), blood coagulation Kalghatgi et al, 2007;Kieft et al, 2005), tissue sterilization Shashurin et al, 2008), and the ablation of cultured liver cancer cells (Zhang et al, 2008). The effects of cold atmospheric plasma were shown to be due not to heat, but to active species, mainly oxygen/hydroxyl radicals and nitric oxide, generated in the plasma or in the tissue brought into contact with the plasma (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stoffels et al developed a RF plasma jet called the "plasma needle," 10 which was extensively used in biomedical applications. 11 Among several other plasma jets that have been developed, [12][13][14][15][16] those which employ simple and nonexpensive voltage generators are attractive for biological or medical application not requiring a very strict control of the thermal load on the gas carrier. A comprehensive review, which gives a description of different plasma jet configurations and biomedical applications, was recently presented by Park et al 17 In particular, Li et al presented recently an atmospheric pressure jet driven by an a-c transformer operated at 50 Hz.…”
Section: And References Therein)mentioning
confidence: 99%
“…2,[29][30][31][32] Since the critical radicals to cell death are O, NO, and OH radicals, the richness of these species may make the plasma jets suitable for biomedical applications. [33][34][35] The excitation temperatures of He or Ar lines were measured by using the Boltzmann plot -method. [36][37][38] The atomic emission intensity (I pq ) of the transition from level p to level q depends on the transition probability (A pq ) and absolute population of the atomic level (n p ), as shown in the following equation; I pq = n p A pq hν(where h is the Planck constant and ν is the photon frequency corresponding to the p→q transition).…”
Section: B Optical Characteristicsmentioning
confidence: 99%